2018
DOI: 10.1126/sciadv.aat3834
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of JAK activation loop phosphorylation is linked to type I JAK inhibitor withdrawal syndrome in myelofibrosis

Abstract: Pathological drug withdrawal syndrome is linked to accumulation of JAK2 phosphorylation in V617F myelofibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 28 publications
12
60
1
Order By: Relevance
“…Recently, Tvorogov et al showed that ruxolitinib induces dose-dependent pJAK2, which can cause life-threatening cytokine-rebound syndrome (due to re-activation of STAT) when the drug is withdrawn [49]. Again, the effect was not apparent when the JAK2 V617F expressing cells were treated with type II inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tvorogov et al showed that ruxolitinib induces dose-dependent pJAK2, which can cause life-threatening cytokine-rebound syndrome (due to re-activation of STAT) when the drug is withdrawn [49]. Again, the effect was not apparent when the JAK2 V617F expressing cells were treated with type II inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…However, type 1 JAK inhibition prevented dephosphorylation and ubiquitination of JAK2, leading to progressive accumulation of an activation loop phosphorylated pool. The phosphorylated pool is rapidly depleted on JAK inhibitor cessation, accounting for the rapid recrudescence of the clinical syndrome known as JAK inhibitor withdrawal syndrome [156].…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…Type 2 JAK2 inhibition occurs when the inhibitor binds to the inactive state at a hydrophobic pocket adjacent to the ATP binding site uncovered by conformational change of the activation loop leading to stabilization of inactive JAK2 [155,157,158]. There is an absence of phosphorylation accumulation and hence no washout seen with type 2 inhibitor withdrawal in vitro [156]. JAK2 inhibitors currently in clinical practice and clinical trials include type 1 inhibitors ruxolitinib, fedratinib, momelotinib and pacritinib [158,159].…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…Inhibitor binding promotes PKB membrane localisation, regulatory site phosphorylation (T308 and S473) by PDK1 and mTORC2, and acquisition of a phosphatase-resistant conformation; consequently, when the inhibitor is removed the 'primed' kinase is fully active [69,6]. Other kinases that undergo 'priming paradoxical activation' (Figure 2) include PKC [70], PKD [71], AMPK [72] and JAK2 [73,74,75]. This mechanism can have severe physiological consequences; for example, a life-threatening cytokine-rebound syndrome occurs when the JAK2 inhibitor, ruxolitinib, is withdrawn too quickly and this is due to priming paradoxical activation of JAK2 [73,74,75].…”
Section: Paradoxical Signalling Induced By Erk5 Kinase Inhibitors Difmentioning
confidence: 99%